How target and perceiver gender affect impressions of HIV risk - Alexander eBarth; Ralf eSchmaelzle; Freda-Marie eHartung; Britta eRenner; Harald T Schupp (Frontiers Media S.A., 2015)
Background: People do not use condoms consistently but instead rely on intuition to identify sexual partners high at risk for HIV infection. The present study examined gender differences of intuitive impressions about HIV risk. Methods: Male and female perceivers evaluated portraits of unacquainted male and female targets regarding their risk for HIV, trait characteristics (trust, responsibility, attractiveness, valence, arousal, and health) and willingness for interaction. Results: Male targets were perceived as more risky than female targets for both perceiver genders. Furthermore, male perceivers reported higher HIV risk perception for both male and female targets than female perceivers. Multiple regression indicated gender differences in the association between person characteristics and HIV risk. In male targets, only trustworthiness predicts HIV risk. In female targets, however, HIV risk is related to trustworthiness, attractiveness, health, valence (for male perceivers), and arousal (for female perceivers).Conclusion: The present findings characterize intuitive impressions of HIV risk and reveal differences according to both, target and perceiver gender. Considering gender differences in intuitive judgments of HIV risk may help devise effective strategies by shifting the balance from feelings of risk towards a more rational mode of risk perception and the adoption of effective precautionary behaviors.